Students’ perceptions of teachers’ teaching and interactions with students: Voices from a Tsunami affected school in Banda Aceh - Fadliadi Ubit (Studies in English Language and Education, 2017)
Casualties and physical destruction of the 2004 tsunami in Aceh are well documented in the literature. However, little is known about lives of teachers and students after the tragedy, particularly about the teaching and learning including teacher-student instructional relationships at the affected schools in the province. This cross-sectional qualitative case study, which was conducted between April and October 2010 at a public junior high school in Banda Aceh that was severely affected by the Aceh 2004 tsunami, provided evidences that the tragedy affected the quality of teachers’ teaching and teacher-student relationships. Data were obtained from semi- structured interviews with ten students from the school, supported by data collection observations over a period of six months. In general, the students commented about their teachers in negative terms. This included students’ deficit views about teachers’ lack of commitment on their teaching practice and their poor interactions with students at the school, affecting the quality of students’ learning at the school.